Feminism and anthropology - Moore Henrietta L (Minneapolis Univ. of Minnesota, 1995)
Chapter 1 discusses the history of the relationship between feminism and anthropology. Chapter 2 deals with debates on gender sexual asymmetry & male dominance. Chapter 3 discusses the relationship between Marxist and feminist anthropology. Chapter 4 deal
Keywords: Ethnology-philosophy; Feminist anthropology; Sex role; Women